Online Training to Build a Mastery Goal Orientation for Youth in the New Normal - Farida Agus Setiyawati; Yulia Ayriza; Kartika Nur Fathiyah; Vera Nur Choirina; Samsul Ariski; Sharifa Rizqi Amalia (IAIN AMBON, 2022)
Community service is an activity that aims to help the community in several activities. This form of activity is designed in the form of online training. Since the outbreak of the pandemic due to the coronavirus, the government has established a lockdown policy or isolation of areas in certain areas. The impact of the pandemic due to Covid-19 has limited youth activities. One of the limited activities is learning activity. Althougt can be improve by online learning, also allows for a negative impact on adolescents who do not have a positive goal orientation. The purpose of this PPM is to build youth self-orientation in the Purwomartani area, Kalasan, Yogyakarta to be more positive with mastery-oriented or more focused on achievement development. The method used in this Community Service is to provide Online Training using the Zoom or Google Classroom application combined with the meet program so that you can interact face-to-face, the activity is carried out 2 times. The increase of the mean score on all components after online training indicates that the activities carried out by the service team can provide increased self-recognition, goal setting and goal orientation, but the low of gain score between the pre and post tests indicates that the increase of goal orientations is less effective. Thus, the activity can be increased with a longer time and better management in order to get maximum results.Keyword: goal orientation, mastery, youth